The Mobilization and Utilization of Scientific and Technological Human Resources in Developing Countries - Michel J Moravscik (ASEAN Journal on Science and Technology for Development, 1986)
Human resources (henceforth abbreviated as "manpower") in the development and the functioning of science and technology in developing countries is the most crucial ingredient, and forms, most often, the bottleneck in evolution. This is so because it takes an extended period of time (decades) to establish an indigenous scientific and technological manpower of sufficient quality and quantity, and because it is a much more difficult and uncertain undertaking to do so than to asquire sufficient financial resources. For this reason problems related to the generation and utilization of scientific and technological manpower are at the very centre of attantion when it comes to managing science and technology in developing countries.